PENERAPAN ISLAMIC MARKETING STRATEGY DAN ISLAMIC HUMAN RESOURCE MANAGEMENT DI UB. SURYA MADIUN - Nur Fauziah (Institut Agama Islam Negeri Ponorogo, 2021)
Surya Madiun is a company engaged in the retail sector, namely minimarkets that provide basic daily needs. At UB. Surya Madiun in implementing the company's activities uses a sharia-based marketing strategy system and Islamic Human Resource Management to improve the quality of the company. This research was conducted to find out how the implementation of Islamic Marketing Strategy and Islamic Human Resource Management in UB. Surya Madison. In this analysis, qualitative data analysis method is used, namely by interviewing parties from UB. Surya Madison. In field research procedures that produce descriptive data, in the form of written or oral data from the people or observed behavior. Therefore, in this study, every symptom related to Islamic Marketing Strategy and Islamic Human Resource Management in UB. Surya Madiun will be thoroughly researched and endeavored to give meaning to every phenomenon found. Surya Madiun adalah sebuah perusahaan yang bergerak di bidang peretailan, yaitu minimarket yang menyediakan kebutuhan pokok sehari-hari. Di UB. Surya Madiun dalam pelaksanaan kegiatan perusahaan menggunakan sistem strategi pemasaran berbasis syariah serta Manajemen Sumber Daya Manusia yang Islami guna peningkatan kualitas perusahaan. Penelitian ini dilakukan guna mengetahui bagaimana penerapan Islamic Marketing Strategy dan Islamic Human Resource Management di UB. Surya Madiun. Dalam analisis ini menggunakan metode analisis data kualitatif, yaitu dengan cara mewawancarai pihak dari UB. Surya Madiun. Dalam prosedur penelitian lapangan yang menghasilkan data deskriptif, berupa data tertulis atau lisan dari orang-orang atau perilaku yang diamati. Oleh karena itu dalam penelitian ini dari setiap gejala yang terkait dengan Islamic Marketing Strategy dan Islamic Human Resource Management di UB. Surya Madiun akan diteliti secara menyeluruh serta diupayakan untuk memberikan makna dalam setiap fenomena yang ditemukan.